On the Performance of Portable NiMH Batteries of General Use - Diego F. Quintero Pulido; Catalin Felix Covrig; Matthias Bruchhausen (Batteries)
NiMH batteries are the most used technology of rechargeable batteries sold directly to consumers. Herein, we study the performance of the most common sizes of portable NiMH batteries (AA, AAA, D, C, and 9V). The performance and durability parameters—capacity, charge retention, charge recovery, and endurance in cycles—are measured for these types of batteries, according to the standard IEC 61951-2:2017 NiMH batteries. The purpose of this study is to create a basis for setting minimum performance requirements for the parameters in the European Regulation concerning batteries and waste batteries, EU 2023/1542, Annex III, Part B. Results show that the charging time of 16 h could be reduced to 8 h for verifying the rated capacity. The performance of commercial batteries with regard to charge retention, charge recovery, and endurance in cycles is often found to be 25–30% better than required in the relevant IEC standard. Furthermore, we present a short comparative analysis of an application test (IEC 60086-2:2021 “toy”) for portable NiMH batteries with primary batteries. Such data allow comparing the performance of portable NiMH batteries compared to primary batteries in the application test “toy”.